Spirituality of Education Leadership to Improve the Quality of High School in the Bible Perspective - Hasibun Asikin; Yakin A. Asikin (East Asian Journal of Multidisciplinary Research, 2022)
Biblical perspective, in particular (Genesis 1:26; 1 Timothy 3:1-7 and 3:8-13). This study aims to explain the general behavior of formalistic, bureaucratic Catholic leadership, less than optimal performance of school principals and improving the quality of education. The focus of the problem in this study is directed at the spirituality of Catholic education in realizing increased performance in high school. This objective portrays the spirituality of leadership that is played by supporting and inhibiting factors in realizing quality through improving performance. The research process was carried out by identifying phenomena, facts, and information on the spirituality of the leadership of the Giovanni Catholic High School Kupang City. Recruitment recommendations for prospective principals are carried out through a fit and proper test directed at principals who have integrity, characteristics, intellect, competence, experience, acceptability, and commitment to achievement. vision and mission of the organization based on religious spiritual values.